Dynamic Analysis of FG Shaft with SMA Supports - K. Udayanand (Defence Science Journal, 2025)
Vibration control has been given paramount importance in industries and defence applications for the efficient functioning of all rotating machinery and to minimize vibration transmission. In defence applications, a significant percentage of vibration is contributed by rotating and reciprocating machinery. The vibration of machinery is crucial from a stealth perspective. Since vibration results in structure-borne sound power, it is predominantly transmitted to a sound-carrying structure from a source via multiple contact points to the underwater environment, leading to the detection of ships and submarines. Consequently, noise and vibrations propagate through the structure, potentially causing sensitive equipment to vibrate or generate undesired radiated noise. The resultant vibration levels of heavy-duty and high-capacity machinery are higher compared to low-capacity machines. In principle, the magnitude of vibration can be reduced through measures at the source, during transmission, while propagating, or at radiation. The machinery parts that significantly affect overall vibration can be reengineered to introduce controls at the source. A concept of Functional Graded Material (FGM) can be proposed for the shafts of machines to reduce overall vibration by varying the material composition based on a gradient index (K) and providing damping in the system. This concept yields effective results when implemented in thermal environments, such as the engine compartments of ships and submarines. The main advantage of using FGMs instead of traditional materials is that the internal composition of their component materials can be tailored to meet the requirements of a specific structure. FGMs are increasingly important as designers seek ways to address structures under combined mechanical and thermal loads. Similarly, vibration levels can be reduced by implementing measures in the transmission path.....